Projected ozone trends and changes in the ozone-precursor relationship in the South Coast Air Basin in response to varying reductions of precursor emissions. (1st February 2016) - Fujita, Eric M.; Campbell, David E.; Stockwell, William R.; Saunders, Emily; Fitzgerald, Rosa; Perea, Roberto
ABSTRACT: This study examined the effects of varying future reductions in emissions of oxides of nitrogen (NOx ) and volatile organic compounds (VOC) on the location and magnitude of peak ozone levels within California's South Coast Air Basin (SoCAB or Basin). As ozone formation is currently VOC-limited in the Basin, model simulations with 2030 baseline emissions (−61% for NOx and −32% for VOC from 2008) predict 10–20% higher peak ozone levels (i.e., NOx disbenefit) in the western and central SoCAB compared with the 2008 base simulation. With additional NOx reductions of 50% beyond the 2030 baseline emissions (−81% from 2008), the predicted ozone levels are reduced by about 15% in the eastern SoCAB but remain comparable to 2008 levels in the western and central Basin. The Basin maximum ozone site shifts westward to more populated areas of the Basin and will result potentially in greater population-weighted exposure to ozone with even a relatively small shortfall in the required NOx reductions unless accompanied by additional VOC reductions beyond 2030 baseline levels. Once committed to a NOx -focused control strategy, NOx reductions exceeding 90% from 2008 levels will be necessary to attain the ozone National Ambient Air Quality Standards (NAAQS). The findings from this study and other recent work that the current VOC emission estimates are underestimated by about 50% suggest that greater future VOC reductions will be necessary to reach the projected 2030 baseline emissions. Increasing the base year VOC emissions by a factor of 1.5 result in higher 2008 baseline ozone predictions, lower relative response factors, and about 20% lower projected design values. If correct, these findings have important implications for the total and optimum mix of VOC and NOx emission reductions that will be required to attain the ozone NAAQS in the SoCAB. Implications : Results of this study indicate that ozone levels in the western and central SoCAB would remain the same or increase with even a relatively small shortfall in the projected NOx reductions under planned NOx -focused controls. This possibility, therefore, warrants a rigorous analysis of the costs and effects of varying reductions of VOC and NOx on the formation and combined health impacts of ozone and secondary particles. Given the nonlinearity of ozone formation, such analyses should include the implications of gradually increasing global background ozone concentrations and the Basin's topography and meteorology on the practical limits of alternative emission control strategies.